Application of chemical products on overcoming the endodormancy in pear trees in regions of low cold unities - Formolo R.* (2010)
The pear is the third temperate fruit specie more consumed in Brazil. However, the expansion of this species requires the development of modern cultural techniques to allow proper cultivation. The objective of the present study was to evaluate the effect of different chemical products to overcome endodormancy of cultivar 'Santa Maria' pear (Pyrus communis L.) in Southern Brazil. The experiment was conducted at the Frutirol orchards in the city of Vacaria, Rio Grande do Sul State (28°29'27.12" S, 50°56'09.78" W). The following formulates were used: Dormex® (Hydrogen Cyanamide H 2CN2) at 0.7% + mineral oil 3%; Dormex® 0.3% + mineral oil 3%; potassium nitrate 10% + mineral oil 3%. Control trees were sprayed only with water. The experimental design was completely randomized, with ten replicates, the experimental unit was a single tree with two selected branches. The number of buds was counted on the day of application and 60 days after to determine bud break rate. The number of fruits was counted the 09/01/2008. The obtained results showed that the use of the two dormancy breaking agents is necessary to standardize the bud break and the harvest in cultivar 'Santa Maria' pear. Dormex® at 0.7% + mineral oil 3% allowed the best result for bud break and fruit number.